Meta-Analysis of Public Trust in the Implementation of the COVID-19 Vaccination Based on the Health Belief Model - Ade Amallia; Agus Syukron Ma'ruf; Isna Nur Rohmah (Masters Program in Public Health, Sebelas Maret University, 2021)
Background: Coronavirus Disease 2019 (COVID-19) is an infectious disease caused by Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2). The magnitude of the global spread of COVID-19, and the declaration by the WHO as a public health emergency pandemic, has created an urgent need for rapid diagnosis, vaccines and therapies for COVID-19. This study aims to determine the relationship between perceptions of COVID-19 and vaccination with the Health Belief Model theory approach, one of which is perceived benefit, with the acceptance of COVID-19 vaccination.Subjects and Method: This study uses a systematic review and meta-analysis with PICO, population: people with an age range of 18-65 years. Intervention: health belief model. Comparison: not health belief model. Outcome: Receiving the COVID-19 Vaccine (Perceived Benefit). The articles used were obtained from several databases, namely Google Scholar, Pubmed, Science Direct, MDPI. The article search keywords were “Health Belief Model” AND “vaccination COVID-19” OR COVID-19 vaccine” AND “COVID-19” The inclusion criteria for research articles were full-text articles using a cross-sectional study design, community research subjects with a range of aged 18-65 years, with the result of the study being receiving the COVID-19 Vaccine (Perceived Benefit) after which a multivariate analysis was carried out with adjusted Odds Ratio (aOR). Data were analyzed using the Review Manager application (RevMan 5.4).Results: A total of 9 cross-sectional studies involving 31,055 vaccine recipient communities spread across Bangladesh, China, South Asia, Hong Kong and Malaysia were selected for a systematic review and meta-analysis. The data collected showed that a person with a high level of confidence in the benefits of the vaccine had a major influence on the acceptance of the COVID-19 vaccine as much as 3.96 times compared to someone with no confidence in the benefits of the COVID-19 vaccine (aOR = 3.97; CI 95 % = 2.62 to 6.02; p < 0.001).Conclusion: People with a high level of confidence in the benefits of the COVID-19 vaccine can increase the impact of receiving the COVID-19 vaccine.Keywords: health belief model, COVID-19 vaccine, vaccine acceptanceCorrespondence:Ade Amallia. Study Program of Prosthetic Orthotic, Health Polytechnics, Ministry of Health Surakarta. Jl. Letjen Sutoyo, Mojosongo, Jebres, Surakarta, Central Java 57127. Email: amalliaadelia@gmail.com. Mobile: 081228466836.Journal of Health Promotion and Behavior (2021), 06(04): 298-306DOI: https://doi.org/10.26911/thejhpb.2021.06.04.04